Morphological changes in the seminal receptacle during ovarian development in the speckled swimming crab Arenaeus cribrarius - Zara, Fernando Jose [UNESP]; Pereira, Gerson Rodrigues Raggi [UNESP]; Sant’anna, Bruno Sampaio (University of Chicago Press, 2014)
To understand sperm plug dissolution and spermatophore dehiscence in Portunidae, histological and ultrastructural changes in the seminal receptacle (SR) of Arenaeus cribrarius were investigated during ovarian development. In juvenile females the SR was filled with acid polysaccharides and the dorsal epithelium was stratified. Mated females with rudimentary ovaries showed a large SR filled by a glycoprotein sperm plug. This plug was present until the developing-ovary stage, when spermatophore dehiscence and intense holocrine secretions in the dorsal dense layer occurred. The plug was absent after the intermediate stage, and the SR became flaccid. The secretion produced moved the spermatophores into the ventral region. The modified dorsal epithelium in the transition between the dorsal and ventral regions released acid polysaccharides, which were found among the sperm, by exocytosis. The morphological changes of the SR in A. cribrarius, including the presence of the sperm plug, followed the macroscopic pattern observed in other members of Portunidae, such as blue crabs. However, in this species dissolution of the sperm plug was synchronized with ovarian development and occurred simultaneously with spermatophore dehiscence, showing the evolutionary relationship of the seminal receptacle and the female reproductive system to the storage of spermatophores and spermatozoa.
Keywords: Developmental stages: DE, developing; INT, intermediate; JUV, juvenile; MAT, mature; OV ovigerous; RUD rudimentary; SR, seminal receptacle